Clinical Manifestations and Hematological Profiles of Pediatric Acute Myeloblastic Leukemia Patients: 3 Years Observational Study in A West Java Tertiary Hospital, Indonesia - Agustinus Wiraatmadja; Nur Suryawan Hidayat; Adhi Kristianto Sugianli (Faculty of Medicine Universitas Padjadjaran, 2019)
Objective: To determine and describe the clinical manifestations and hematological profiles of pediatric Acute Myeloblastic Leukemia (AML) in Dr. Hasan Sadikin General Hospital (RSHS), Bandung as a tertiary hospital in West Java, Indonesia.Methods: A retrospective cross-sectional study using the total sampling method was performed on the medical records of pediatric patients (0-18 years old)who were diagnosed as AML for the first time through bone marrow examination during the period of January 1, 2015 – December 31, 2017. Results: Of the 54 subjects who met the inclusion criteria, 42.6% were AML patients in the age group 6-12 years with male patients comprised 59.3% of the total number of subjects. Patients generally experienced pallor (83.3%), fever (75.9%), and decreased appetite (70.4%). The hematological profiles showed that 35.2% of patients had Hb <6.5 g/dL and 44.4% had a leukocyte count of of >50,000 cells/mm3. The majority of the subjects had a platelet count of <50,000 cells/mm3 (83.3%) and almost half of them had a peripheral blasts count of >50% (46.3%). Conclusion: Clinical manifestations and hematological profiles are important to diagnose AML, especially in pediatric patients. By assessing the manifestations and profiles, it is feasible to access and detect suspected cases of AML.